Interior Design of the Bahurekso Kendal Cultural House in Kendal Regency - Taufik Chandra Nugroho; Sumarno Sumarno (Pendhapa, 2022)
The Interior Design of the Bahurekso Kendal Cultural House, located in Kendal Regency, is a special interior design aimed at artists in Kendal City, as a forum for the community or art activists in Kendal Regency as a facility for expression or performance. Art activists can promote or introduce studios and cultural arts from each region in Kendal Regency. The interior design of the Bahurekso Kendal Cultural House adopts the John M. Kurtz programming method which consists of orientation, basic programming, repetition of programming, until the design reaches approval. The design basis used is a theme and style approach, a function approach, an ergonomics approach, and a color approach. The interior design of the Bahurekso Kendal Cultural House features Barong Loreng Genteng, an art that is loved by the citizens of Kendal City. The Barong Loreng Genteng theme was chosen with the consideration that the interior space-filling elements will lead to the traditional aspect. The Barong Loreng Genteng theme is achieved through shapes, materials and colors. The scope of work on the design includes the lobby, auditorium, make-up room, art gallery, player transit room, stage staff room, office, dance practice room, library, caffe, and open stage. able to make it as a means of folk entertainment culture and educational facilities in order to preserve traditional art culture, especially in Kendal Regency. The character of the space is very helpful in creating comfort and safety for visitors.